Про зміст термінів “інтродукція” та “акліматизація” деревних рослин - Gorb, V.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
In this paper, we suggest to use the term «acclimatized » only for tree species, whose genotypes may have been changed due to introduction only within the range of its spontaneous polymorphism, not due to hybridization or mutagenesis. Thus, acclimatization is the process of adaptation of a species to new environmental conditions because of the appearance of resistant individuals with the genotype resulted from spontaneous intraspecific hybridization within its offspring. In contrast, introduction is the process of scientifically founded selection of plants material of the species for the initial breeding outside of the species areal. It is emphasized that the diversity in the taxonomical composition of cultivars may be increased due to the interspecific hybridization of introduced species. However, specimens obtained using this method should have hybrid status.